Genus Cyptophania Banks (Psocodea: ‘Psocoptera’: Lepidopsocidae): unique features, augmented description of the generotype, and descriptions of three new species - Mockford, Edward L.; Wynne, J. Judson (Zootaxa, 2013)
We define the genus Cyptophania with characters that clearly separate it from other genera of the Family Lepidopsocidae in which wing reduction has occurred. We redescribe the generotype, C. hirsuta Banks (Hawaii, presumably introduced), and describe three new species, C. australica n.sp. (Queensland, Australia), C. costalis n.sp. (Gulf of Mexico and Caribbean), and C. pakaratii n.sp. (Rapa Nui = Easter Island, probably endemic). The latter species is described from both sexes and presents the first males known for the genus. One female of this species presents a large spermatophore protruding from the genital chamber, thus indicating the mode of sperm transfer in sexual members of this genus. A key to the known species is included. All of the species of Cyptophania are highly neotenic, but differences in the level of neoteny are noted among the species studied. We question the synonymy of the genus Ptenocorium Enderlein with Cyptophania on the basis of several characters illustrated in the original description of Ptenocorium. We note similarities of Cyptophania to the entirely macropterous genus Lepidopsocus Enderlein and suggest a possible close relationship between the two genera.